Measurements by controlled meteorological balloons in coastal areas of Antarctica. Issue 5 (6th June 2016) - Hole, Lars R.; Bello, Alexis Pérez; Roberts, Tjarda J.; Voss, Paul B.; Vihma, Timo
Abstract: An experiment applying controlled meteorological (CMET) balloons near the coast of Dronning Maud Land, Antarctica, in January 2013 is described. Two balloons were airborne for 60 and 106 hours with trajectory lengths of 885.8 km and 2367.4 km, respectively. The balloons carried out multiple controlled soundings on the atmospheric pressure, temperature and humidity up to 3.3 km. Wind speed and direction were derived from the balloon drift. Observations were compared with radiosonde sounding profiles from the Halley Research Station, and applied in evaluating simulations carried out with the weather research and forecasting (WRF) mesoscale atmospheric model. The most interesting feature detected by the CMET balloons was a mesoscale anticyclone over the Weddell Sea and the coastal zone, which was reproduced by the WRF model with reduced intensity. The modelled wind speed was up to 10 m s -1 slower and the relative humidity was 20–40% higher than the observed values. However, over the study period the WRF results generally agreed with the observations. The results suggest that CMET balloons could be an interesting supplement to Antarctic atmospheric observations, particularly in the free troposphere.